Imaging Mouse Development with Confocal Time-Lapse Microscopy - Nowotschin, Sonja (2010)
The gene expression, signaling, and cellular dynamics driving mouse embryo development have emerged through embryology and genetic studies. However, since mouse development is a temporally regulated three-dimensional process, any insight needs to be placed in this context of real-time visualization. Live imaging using genetically encoded fluorescent protein reporters is pushing the envelope of our understanding by uncovering unprecedented insights into mouse development and leading to the formulation of quantitative accurate models.